Rural Teachers' Perceptions of the Effectiveness of Various Supervisory Practices - James Levin; Nancy Hoffman; Bernard J. Badiali (Journal of Research in Rural Education, 1987)
Data on supervisory practices in four rural school districts in central Pennsylvania were gathered from elementary and secondary teachers using the Survey for Supervisory Practices. The survey includes questions related to the frequency, purpose and perceived value of supervision. One item, "The Supervision I Received Was Helpful to My Improvement as a Teacher" was used as the dependent variable to test sixteen independent variables using analysis of variance (ANOVA) and Duncan's Mean Separation Procedure. Null hypotheses concerning teachers' perceptions that supervision was helpful-were rejected for five independent variables. Teachers (N= 549) indicated that they perceive supervision to be helpful when (I) they understand that the purpose of supervision is to assist them in improving their teaching; (2) they and supervisors jointly identify instructional changes; (3) the supervisor is able to get them to focus on their teaching; (4) the supervisor is knowledgeable about the teachers' instructional objective; and (5) they were observed enough by the supervisor.